Yijinjing Qigong intervention shows strong evidence on clinical effectiveness and electroencephalography signal features for early poststroke depression: A randomized, controlled trial - Sun, Pingping; Zhang, Shuaipan; Jiang, Linhong; Ma, Zhenzhen; Yao, Chongjie; Zhu, Qingguang; Fang, Min (Frontiers in Aging Neuroscience, 2022)
ABSTRACT Objective: Although Traditional Chinese Yijinjing Qigong Exercise (YJJQE) as a mind-body intervention is popularly used among adults to ameliorate depressive symptoms in China, no randomized controlled trials (RCTs) are available to evaluate the effects of YJJQE in patients with poststroke depression (PSD). This study aims to explore the clinical efficacy and the neurological and psychiatric mechanism in brain network functional connectivity underlying electroencephalography (EEG). Methods: A total of 60 patients diagnosed with mild PSD are randomly (1:1) assigned to YJJQE Qigong group (n=30) and control group of routine segmental rehabilitation training group (n=30) for a 60-minute exercise session once a day for 3 weeks. All outcome measures were collected at baseline and 3-week ending intervention. The primary outcome was the 24-item Hamilton Depression Scale (HAMD-24) score, evaluation at more time points for one month of follow-up. The secondary outcomes were EEG data in four frequency domains (δ, θ, α, β), global efficiency (GE), local efficiency (LE), GE/LE curve (AUC), and Phase Lag Index (PLI). Results: All patients showed no significant differences in baseline data. After 3 weeks and one month of follow-up, the YJJQE group demonstrated significant decreasing changes compared to the control group on the HAMD-24 scores (P< 0.001). In addition, the YJJQE group also showed a significant reduction in θ wave and increasing in GE and LE. Compared to the control group, the YJJQE Qigong group showed significantly greater functional connectivity in δ, θ, and β frequency bands in the brain network of the degree of phase synchronization (P< 0.001). Conclusion: Our findings demonstrated that YJJQE may effectively alleviate the depressed mood of patients with PSD by promoting the efficiency in information transmission of network functional connectivity and its integration ability in different brain regions. Therefore, the YJJQE would be a useful nonpharmacological treatment to prevent PSD.